Upper gastrointestinal endoscopy procedure volume trends, perioperative mortality, and malpractice claims : Population-based analysis - Nurminen, Nelli; Järvinen; Tommi; Robinson; Eric; Zhou, Nanruoyi; Salo, Silja; Räsänen, Jari; Kytö, Ville; Ilonen, Ilkka (Thieme, 2025)
Background and study aims Upper gastrointestinal endoscopy (EGD) is one of the most common diagnostic procedures done to examine the foregut, but it can also be used for therapeutic interventions. The main objectives of this study were to investigate trends in EGD utilization and mortality related to it in a national low-threshold healthcare system, assess perioperative safety, and identify and describe patient-reported malpractice claims from the national database.
Patients and methods We retrospectively identified patients from the Finnish Patient Care Registry who underwent diagnostic or procedural EGD between 2010 and 2018. In addition, patient-reported claims for malpractice were analyzed from the National Patient Insurance Center (PIC) database. Patient survival data were gathered collectively from the National Death Registry from Statistics Finland.
Results During the study period, 409,153 EGDs were performed in Finland for 298,082 patients, with an annual rate of 9.30 procedures per 1,000 inhabitants, with an annual increase of 2.6%. Thirty-day all-cause mortality was 1.70% and 90-day mortality was 3.84%. For every 1,000 patients treated, 0.23 malpractice claims were filed.
Conclusions The annual rate of EGD increased by 2.6% during the study, while the rate of interventional procedures remained constant. Also, while the 30-day mortality rate declined over the study period, it is an unsuitable quality metric for EGDs in comprehensive centers because a patient's underlying disease plays a larger role than the procedure in perioperative mortality. Finally, there were few malpractice claims, with self-evident causes prevailing.